PENGARUH PENDEKATAN CONCRETE PICTORIAL ABSTRACT (CPA) TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS III SD NEGERI 293 TANAH KONGKONG KABUPATEN BULUKUMBA - Zahra Ramadani; Rahmawati Patta; Hardianto Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low understanding of mathematical concepts among third-grade elementary school students. The study aimed to determine the implementation of the Concrete-Pictorial-Abstract (CPA) approach, describe students’ understanding of mathematical concepts, and examine the effect of the CPA approach on students’ understanding of mathematical concepts. This research used a quantitative approach with a pre-experimental method and a One Group Pretest-Posttest Design. The population consisted of all third-grade students of SD Negeri 293 Tanah Kongkong, Bulukumba Regency, with a sample of 24 students selected using saturated sampling technique. Data were collected through observation sheets and mathematical concept understanding tests. Data analysis techniques used descriptive and inferential statistics through the t-test. The results showed that: (1) the implementation of the CPA approach in mathematics learning was categorized as very good, (2) students’ understanding of mathematical concepts increased and was categorized as high after the implementation of the CPA approach, and (3) there was a significant effect of the Concrete-Pictorial-Abstract (CPA) approach on students’ understanding of mathematical concepts, indicated by a significance value less than 0.05. Therefore, the CPA approach can be used as an effective alternative in improving elementary school students’ understanding of mathematical concepts.